2003
DOI: 10.1073/pnas.1033133100
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial DNA replication by zinc mobilization during nitrosative stress

Abstract: Phagocytic cells inhibit the growth of intracellular pathogens by producing nitric oxide (NO). NO causes cell filamentation, induction of the SOS response, and DNA replication arrest in the Gramnegative bacterium Salmonella enterica. NO also induces doublestranded chromosomal breaks in replication-arrested Salmonella lacking a functional RecBCD exonuclease. This DNA damage depends on actions of additional DNA repair proteins, the RecG helicase, and RuvC endonuclease. Introduction of a recG mutation restores bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 52 publications
2
92
0
1
Order By: Relevance
“…Thus, when used at a high concentration (35 nmol/ml/min vs. Ϸ0.5 nmol/ml/min in our experiments), NO may act as an inducer of the SOS response in E. coli (31); in these conditions, the recA deletion leads to a high sensitivity to NO (31), demonstrating that the SOS response is induced and essential to fight the deleterious effects of NO. Nevertheless, ''physiological'' amounts of NO do not stimulate the SOS response in Salmonella enterica because RecA is not essential to prevent NO-dependent bacterial DNA fragmentation (32). Moreover, several transcriptomic analysis of E. coli demonstrated that expression of the genes of the SOS response was not enhanced following exposure to NO (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when used at a high concentration (35 nmol/ml/min vs. Ϸ0.5 nmol/ml/min in our experiments), NO may act as an inducer of the SOS response in E. coli (31); in these conditions, the recA deletion leads to a high sensitivity to NO (31), demonstrating that the SOS response is induced and essential to fight the deleterious effects of NO. Nevertheless, ''physiological'' amounts of NO do not stimulate the SOS response in Salmonella enterica because RecA is not essential to prevent NO-dependent bacterial DNA fragmentation (32). Moreover, several transcriptomic analysis of E. coli demonstrated that expression of the genes of the SOS response was not enhanced following exposure to NO (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of nitric oxide, S. enterica requires RecBC but not RecA for viability and undergoes RuvABC-dependent chromosome breakage in the recB background. These observations led to the proposal that upon infection, the inhibition of S. enterica replication by macrophageproduced nitric oxide causes replication fork reversal, which is lethal for the S. enterica recB mutant and thus accounts for its decreased virulence (63). Despite a high conservation of structure and function of replication and recombination proteins, replication arrests in eukaryotes will clearly have consequences different from those in prokaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…Another example of replication fork reversal in bacteria was observed in Salmonella enterica serovar Typhimurium, a close relative of E. coli. A recB derivative of S. enterica is highly attenuated for virulence (63). The nitric oxide produced by macrophages when they ingest S. enterica causes bacterial replication inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial targets of RNI include thiols, metal centers, lipids and DNA. NO itself is considered to be bacteriostatic and NO-related toxicity includes inhibition of respiration [3] and reduced cell division by disrupting DNA replication [4]. In approximately 80 % of the community-acquired urinary tract infections (UTIs) the cause of the infection is a uropathogenic Escherichia coli (UPEC) strain.…”
mentioning
confidence: 99%